Testing tubewell platform color as a rapid screening tool for arsenic and manganese in drinking water wells - Biswas, A.; Nath, B.; Bhattacharya, P.; Halder, D.; Kundu, A.; Mandal, U.; Mukherjee, Abhijit; Chatterjee, D.; Jacks, G. (American Chemical Society, 2012)
A low-cost rapid screening tool for arsenic (As) and manganese (Mn) in groundwater is urgently needed to formulate mitigation policies for sustainable drinking water supply. This study attempts to make statistical comparison between tubewell (TW) platform color and the level of As and Mn concentration in groundwater extracted from the respective TW (n = 423), to validate platform color as a screening tool for As and Mn in groundwater. The result shows that a black colored platform with 73% certainty indicates that well water is safe from As, while with 84% certainty a red colored platform indicates that well water is enriched with As, compared to WHO drinking water guideline of 10 µg/L. With this guideline the efficiency, sensitivity, and specificity of the tool are 79%, 77%, and 81%, respectively. However, the certainty values become 93% and 38%, respectively, for black and red colored platforms at 50 µg/L, the drinking water standards for India and Bangladesh. The respective efficiency, sensitivity, and specificity are 65%, 85%, and 59%. Similarly for Mn, black and red colored platform with 78% and 64% certainty, respectively, indicates that well water is either enriched or free from Mn at the Indian national drinking water standard of 300 µg/L. With this guideline the efficiency, sensitivity, and specificity of the tool are 71%, 67%, and 76%, respectively. Thus, this study demonstrates that TW platform color can be potentially used as an initial screening tool for identifying TWs with elevated dissolved As and Mn, to make further rigorous groundwater testing more intensive and implement mitigation options for safe drinking water supplies. © 2011 American Chemical Society.